Phosphorus adsorption in lowlands of Santa Catarina cultivated with rice and its relation with soil properties - Simonete, Marcia; Ernani, Paulo; Teixeira-Gandra, Claudia Fernanda; Moro, Letícia (Revista Ciência Agronômica, 2018)
Soils have different capacities to retain phosphorus (P). In seasonal flooded soils iron (Fe) oxides and hydroxides of poor crystallinity, increase with time, and could be the most important constituent in P adsorption, during the time the soils remain unflooded. The present paper had the objective to determine the maximum adsorption capacity of P (MACP), collected from five selected soils in lowland rice areas in the Santa Catarina state, to search for soil individual parameters that best correlates with maximum adsorption capacity of P (MACP). The rates of P used to determine the MACP were calculated based on the concentration of indigenous P in the soil. The sorption of P and the P in solution data were then fitted to the Langmuir sorption isotherm equations. The results obtained for the parameters ´a´ and ´b´ (binding energy and MACP, respectively) were correlated with selected soil parameters. The Langmuir equations adequately described P adsorption in the soils. The maximum sorption of P varied widely, ranging from 0.419 to 1,450 mg g-¹, where the organic soil (OXs) presented very high MACP, which could lead to a less availability of the element to the plants. The coefficients of correlation showed a significant association between MACP and the following soil parameters: P indigenous, Fe oxides extracted with ammonium oxalate at pH 3.0 (Feo3) and pH 6.0 (Feo6), as well as the ratios Feo3/Fed and Feo6/Fed, suggersting that these chemical parameters can be utilized to characterize the P adsorption in these soils.